2002
DOI: 10.1289/ehp.021100593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perinatal exposure to PCBs and dioxins on play behavior in Dutch children at school age.

Abstract: Polychlorinated biphenyls (PCBs) and dioxins are known as neurotoxic compounds that may modulate sex steroid hormones. Steroid hormones play a mediating role in brain development and may influence behaviors that show sex differences, such as childhood play behavior. In this study we evaluated the effects of perinatal exposure to environmental levels of PCBs and dioxins on childhood play behavior and whether the effects showed sex differences. As part of the follow-up to the Dutch PCB/dioxin study at school age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
104
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(114 citation statements)
references
References 43 publications
7
104
1
2
Order By: Relevance
“…Other social-related research has focused on the effects of PCBs on reproductive behavior and fertility [32,33]. One of the recent reports on social behavior described the effects of PCBs on social play interactions in children in a Dutch cohort [34]. This study revealed that boys with a higher level of PCBs scored higher on the feminine scale and lower on the masculine scale of a questionnaire indirectly gauging play activity.…”
Section: Introductionmentioning
confidence: 81%
“…Other social-related research has focused on the effects of PCBs on reproductive behavior and fertility [32,33]. One of the recent reports on social behavior described the effects of PCBs on social play interactions in children in a Dutch cohort [34]. This study revealed that boys with a higher level of PCBs scored higher on the feminine scale and lower on the masculine scale of a questionnaire indirectly gauging play activity.…”
Section: Introductionmentioning
confidence: 81%
“…These results suggest that fish intake and breast milk feeding should not be discouraged. In the same Dutch children cohort at school age, negative effects of prenatal PCBs on cognitive and motor development were observed only in children raised in a poor social environment (Vreugdenhil et al, 2002), although effects of prenatal exposure on cognitive ability were observed in these children at 18 and 42 months of age (Huisman et al, 1995; Dioxin in breast milk and newborn head circumference Nishijo et al et al, 1999). A follow-up study using a larger cohort, to investigate cognitive and motor development with a survey of nutritional and social circumstances, is necessary to clarify the effects of TCDD on head size.…”
Section: Discussionmentioning
confidence: 97%
“…Play behaviour in children is normally seen to reflect their sexes, but research into hormone mimics have shown that these norms can be altered as a result of exposure in the womb or from the environment to chemicals, thus making boys associated with more feminised play behaviour and vice versa. Observations from a Dutch study on children prenatally exposed to PCBs and dioxins shows higher levels of PCBs correlating with less masculinised play in boys while more feminised play behaviour is seen in both sexes after prenatal exposure to dioxins (Vreugdenhil et al, 2002).…”
Section: Effects On Population Changesmentioning
confidence: 93%